Outcomes of robotic right colectomy with intracorporeal anastomosis compared with laparoscopic right colectomy - D. Coco; S. Leanza (Клінічна хірургія)
Outcomes of robotic right colectomy with intracorporeal anastomosis compared with laparoscopic right colectomy